Evaluation of gladiolus (Gladiolus grandiflorus) cultivars for performance and correlation in vegetative, floral and multiplication characters under paired- row system (Current Horticulture, 2024)
The vegetative, floral and corm characters of seven gladiolus cultivars (Friendship, Candyman, White Prosperity, Novalux, Priscilla, Summer Sunshine and Dull Queen) were evaluated under paired-row system to study the performance of cultivars and to find suitable cultivar for cut flower production. The vegetative performance of cultivars Novalux, White Prosperity and Candyman were comparatively better with early shoot emergence in 5.566 days (White Prosperity), maximum plant height of 160.62 cm (White Prosperity), maximum shoots per corm of 1.867 (Novalux) and highest number of leaves (8.33) in cultivar Candyman. The cultivar Priscilla performed superiorly in some major floral characters such as spikes per corm (1.733), early spiking (65.33 days) and vase life (10.73 days). While cultivar White Prosperity was also better performer in some critical floral characters such as florets per spike (16.400), rachis (81.827 cm), florets open at once (6.733), spike length (103.587 cm) and size of florets (10.673 cm). In case of multiplication property, cultivar Dull Queen produced highest number of corms (2.400) and cormels (47.267) while corm size (9.060 cm) and weight (212.133 g) was highest in Novalux. The outcome of the experiment indicated that cultivars White Prosperity, Priscilla and Novalux were best suited under paired-row system for cut flower production and corm and cormel production.
Keywords: Correlation; Paired-row; Floral; Corms; Cormels; Multiplication